A implementação da Lei Geral de Proteção de Dados no setor de corretagem imobiliária de Santana do Livramento - (:unkn) unknown (Universidade Federal do Pampa, 2022)
The present work aims to identify the level of knowledge and what changes were implemented by the real estate brokerage sector (both individual and real estate brokers) in Santana do Livramento/RS to adapt to the General Data Protection Law (LGPD), which came into force in September 2020, but whose administrative sanctions only came into force in August 2021. The hypothesis defined is that the majority of the sector did not make enough changes to adapt to the legislation. To achieve the objective of the monograph, a descriptive practical research was carried out, through responses obtained in the application of a survey in January and February 2022 to realtors in Santana do Livramento. The Approach Method used in the research is the Inductive Method and the Procedure Method was the Monographic Method. Throughout the work, the importance of the security of personal data is contextualized, since the current economy collects and uses this information on a large scale, generating the risk of large leaks and use for abusive purposes. Subsequently, the LGPD and its main elements relevant to the research are presented, including: principles, legal bases that authorize the processing of personal data, the provisions of the National Data Protection Authority (ANPD) and administrative sanctions. In the final chapter, the main points of the questionnaire used are detailed, then the responses obtained from its application are presented and analyzed. The main results indicate that there is little knowledge of certain aspects of the law, in particular about the existence and functioning of the National Data Protection Authority and the administrative sanctions that it can apply to violators, but on the other hand there is already a pratice of consumer data collection through express consent and take precautions to keep the information secure. In this way, there is a concern among professionals with the security of their clients' information, but there are still many challenges for a complete adequacy of the LGPD in the sector, in part due to the lack of knowledge of the legislation.
The implementation of the General Data Protection Law in the Santana do Livramento real estate brokerage sector
Keywords: Proteção de Dados Pessoais; Autodeterminação Informativa; Corretagem Imobiliária; Protection of personal data; The Right to Information Self-Determination; Real Estate Brokerage; CNPQ::CIENCIAS SOCIAIS APLICADAS